Microcredit Access to Change Socio-Economic Status and Economic Empowerment of Women in the Microfinance Industry - Mutuo, Irene (University of Embu, 2020)
The last three decades have globally, regionally and at country level witnessed a greater visibility and attention on gender issues especially women’s empowerment. However the journey to women’s empowerment has faced constraints such as lack of easy access to the funds among others which lead to lower participation of women in micro credit finance and the economy at large as not much can be done without funds. Their contribution to economic growth has been underappreciated and under supported over the years. This study therefore aimed at testing the economic and social activities women engage to bring about empowerment and recognition in today’s world. The majority of them are engaged in small income generating self-employment in agriculture and non-agricultural activities with low prospect for growth. many women in the rural areas prefer investing in farming and making of kiondos with sisal while those in the urban regions where there are more resources would rather get products at low prices and sell them at a reasonable price getting profits which they reinvest and save up for other projects. Women economic empowerment has been recognized as one of means for economic growth poverty reduction. It seeks to increase women access to the factors of production through special credit facilities and other modes of financial access. As a result this tends to reduce the incidence of poverty among them if, well deployed and managed strategies have been put to place. This also increases employment and household income thereby leading to sustainable economic development among women. The objectives include to investigate the level of financial intermediation through microcredit access, social intermediation through subsidized products and social services which include education and health to assess the wellbeing of those individuals and positive impact on their saving power. Rural women’s saving capability differed significantly before and after their membership in microcredit funds. In other words, their membership in these funds had a positive impact on their saving power. The limitations of these study include illiteracy, early marriages, family structures, lack of social awareness and job status. This study will assist reach the different counties, the unbanked as it will provide sensitization and awareness on the Microfinance Institutions products and services. These institutions will provide financial intermediation, social intermediation and social services which will assist the community as a whole. This study also assist women access the different microfinance products and use them to start and expand their businesses which improves their living standards as they are able to sustain their families and provide the basic needs and also education which is a secondary need. This improves their socio economic status and empowers them in the long run.